Junior doctor-designed induction booklet to improve future junior doctor experience in a new post. (2019) - Thomas, Nibu; McGrann, Eoin; Zammit, Louise; Eaton, Patrick; White, William; Lingam, Claire; Thompson, Charlotte; Morgan, Christopher; William, Linda; Davie, Philip; Shellien, Rachel; O'Neill, Ronan
No abstract available